Миоценовые птицы Западного Причерноморья УССР. Сообщение I - Уманская, А.С. (Вестник зоологии, 1979)
The new genus and species of the family Otididae — Miootis compactus gen. et sp. and of the subfamily Anserinae — Proanser major, gen. et sp. are described from the Late Miocene deposits of the Black See area of the Ukrainian SSR. Relationships are established between the fossil and recent forms.